A Critical Reappraisal of the Bleeding Time - Rodgers, R. P. Channing; Levin, Jack (Seminars in Thrombosis and Hemostasis, 2023)
Seminars in Thrombosis and Hemostasis (STH) celebrates 50 years of publishing in 2024. To celebrate this landmark event, STH is republishing some archival material. This manuscript represents the second most highly cited paper ever published in STH. The manuscript published without an abstract, and essentially represented a State of the Art Review on the bleeding time, a relatively invasive procedure that required an incision on the skin or earlobe of a patient, and timing how long it took for the incision to stop bleeding. The bleeding time test was first described in 1901 by the French physician Milian, who presented three studies of bleeding from stab wounds made in the fingertips of healthy and diseased subjects. In 1910, Duke observed the duration of bleeding from small incisions of the ear lobe, and pointed out that the duration of bleeding was increased in instances of reduced platelet counts. The test was subsequently repeatedly modified, and numerous variants of the test, including semiautomated methods, were described by several workers. The most frequently utilised test reflected one described by Ivy and coworkers, who shifted the location of the incision to the volar aspect of the forearm and applied a blood pressure cuff to the arm to maintain a standard venous pressure. The bleeding time has been proposed for use as a diagnostic test for platelet-related bleeding disorders, a measure of efficacy in various forms of therapy, and as a prognosticator of abnormal bleeding. The authors to the current review reevaluated the bleeding time literature using methods to assess the performance of the test in 1990, locating 862 printed documents that discussed the bleeding time, the majority in peer-reviewed professional journals. As this is a republication of archival material, transformed into a modern format, we apologise in advance for any errors introduced during this transformation.
Keywords: skin bleeding time; clinical utility; surgical bleeding risk; platelet count and function; predictor of therapy efficacy